1998
DOI: 10.1148/radiology.206.3.9494506
|View full text |Cite
|
Sign up to set email alerts
|

Congenital muscular dystrophy: use of brain MR imaging findings to predict merosin deficiency.

Abstract: Diffuse white matter changes resembling those seen with leukodystrophy may be a valuable criterion for diagnosis of merosin deficiency in patients with classic congenital muscular dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Other relevant clinical hallmarks of MDC1A include elevated creatine kinase (CK) levels and dystrophic changes (necrosis and regeneration of fibers, chronic inflammation, and fibrosis) recognizable in muscle biopsies of these patients (Tomé et al., ). Diagnostically important features are the complete absence of laminin‐α2 staining evaluated by immunohistochemistry (IHC) performed in muscle or in skin biopsies (Sewry et al., ) using specific antibodies, and typical white matter changes (WMC) in brain detectable by magnetic resonance imaging (MRI; Lamer et al., ). WMC are related with alterations in the brain's water content, due to modifications in the maturation and/or function of the blood–brain barrier, and are detectable after the first six months to one year of life (Menezes et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant clinical hallmarks of MDC1A include elevated creatine kinase (CK) levels and dystrophic changes (necrosis and regeneration of fibers, chronic inflammation, and fibrosis) recognizable in muscle biopsies of these patients (Tomé et al., ). Diagnostically important features are the complete absence of laminin‐α2 staining evaluated by immunohistochemistry (IHC) performed in muscle or in skin biopsies (Sewry et al., ) using specific antibodies, and typical white matter changes (WMC) in brain detectable by magnetic resonance imaging (MRI; Lamer et al., ). WMC are related with alterations in the brain's water content, due to modifications in the maturation and/or function of the blood–brain barrier, and are detectable after the first six months to one year of life (Menezes et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Two Class II studies 31,32 and 1 Class III study 33 demonstrated that abnormal findings on brain imaging studies can predict the subtype-specific diagnosis in some cases, especially in merosinopathy (white matter abnormalities) and some dystroglycanopathies (polymicrogyria, white matter lesions, pontine hypoplasia, and subcortical cerebellar cysts).…”
mentioning
confidence: 99%
“…In this autosomal‐recessive inherited congenital muscular dystrophy merosin, the α 2 laminin subunit, is mutated and either absent or greatly reduced 68–71 . There has been a milder clinical phenotype with a partial protein defect producing a truncated protein 72,73 .…”
Section: Merosinopathy (Figure 2g–i)mentioning
confidence: 99%